2021
DOI: 10.1123/jpah.2021-0187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a National Peer-Led Training Program to Increase Brief Physical Activity Advice Given to Patients by Health Care Professionals

Abstract: Background: The benefits of physical activity for preventing and managing long-term health conditions are well established and health care professionals could promote physical activity to patients. The current study aims to evaluate the impact of the Clinical Champions Physical Activity Training Program. Methods: Health care professionals attend a one-off in-person training session delivered by a trained Clinical Champion. Attendees at the Clinical Champions Physical Activity Training Program were asked to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous literature has indicated that primary care providers might lack knowledge and confidence in discussing and promoting PA among patients (26)(27)(28). However, the current findings suggest that whilst familiarity with the CMO PA guidance remains low, three quarters of GPs felt confident to discuss PA with patients.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous literature has indicated that primary care providers might lack knowledge and confidence in discussing and promoting PA among patients (26)(27)(28). However, the current findings suggest that whilst familiarity with the CMO PA guidance remains low, three quarters of GPs felt confident to discuss PA with patients.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Training programmes, either preprofessional or in-service, show promise in addressing these barriers and in increasing the delivery of physical activity advice to patients 24. Important physical activity topic areas relevant for health professionals’ training have been identified25; however, there is currently no consensus on the specific minimum competencies required by all health professionals to provide movement behaviour change support.…”
Section: Introductionmentioning
confidence: 99%
“…21 Training programmes, either preprofessional or in-service, show promise in addressing these barriers and in increasing the delivery of physical activity advice to patients. 24 Important physical activity topic areas relevant for health professionals' training have been identified 25 ; however, there is currently no consensus on the specific minimum competencies required by all health professionals to provide movement behaviour change support. Further, to date, the focus has been on physical activity promotion, with less literature investigating sedentary behaviour change in healthcare settings, 17 despite sedentary behaviour being a distinct, but related, health behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Time constraints imposed on clinical appointments were identified as another barrier to such provision with NHS cancer care pathways, in accordance with previous findings [ 49 ], which limits delivery options to brief consultant-led conversations within the care pathway. Evidence suggests there is potential to increase the number of brief intervention consultations with appropriate training [ 52 ], consistent with the Making Every Contact Count (MECC) initiative [ 53 ], but this approach is likely to have minimal impact [ 54 , 55 ]. Alternatively, having the opportunity to sign-post/refer women onto credible and motivational weight management information and support after primary treatment was viewed positively by HCPs, as in other studies [ 38 , 42 ], and could help to overcome the challenge of time constraints during consultations.…”
Section: Discussionmentioning
confidence: 99%